2012
DOI: 10.1182/blood-2012-04-420596
|View full text |Cite
|
Sign up to set email alerts
|

Addition of bevacizumab to chemotherapy in acute myeloid leukemia at older age: a randomized phase 2 trial of the Dutch-Belgian Cooperative Trial Group for Hemato-Oncology (HOVON) and the Swiss Group for Clinical Cancer Research (SAKK)

Abstract: An urgent need for new treatment modalities is emerging in elderly patients with acute myeloid leukemia (AML). We hypothesized that targeting VEGF might furnish an effective treatment modality in this population. Elderly patients with AML were randomly assigned in this phase 2 study (n ‫؍‬ 171) to receive standard chemotherapy (3 ؉ 7) with or without bevacizumab at a dose of 10 mg/kg intravenously at days 1 and 15. In the second cycle, patients received cytarabine 1000 mg/m 2 twice daily on days 1-6 with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…34,35 In addition, new therapeutic strategies are being developed, targeting some of these pathways, such as the use of anti-VEGF, alone or in combination with standard chemotherapy, although results are still disappointing. 36 The current study provides new insights into the increasing evidence of the role of HIF-mediated activation pathways on prognosis of patients with myeloid neoplasms. Interestingly, we observed that an enhanced expression for GYS1 and MIF is an independent factor for survival and identified a subgroup of patients with poorer outcome even within the different subgroups of patients evaluated (LR-MDS, HR-MDS, and AML).…”
Section: Discussionmentioning
confidence: 96%
“…34,35 In addition, new therapeutic strategies are being developed, targeting some of these pathways, such as the use of anti-VEGF, alone or in combination with standard chemotherapy, although results are still disappointing. 36 The current study provides new insights into the increasing evidence of the role of HIF-mediated activation pathways on prognosis of patients with myeloid neoplasms. Interestingly, we observed that an enhanced expression for GYS1 and MIF is an independent factor for survival and identified a subgroup of patients with poorer outcome even within the different subgroups of patients evaluated (LR-MDS, HR-MDS, and AML).…”
Section: Discussionmentioning
confidence: 96%
“…However, therapeutic outcomes of angiogenesis inhibitors in AML have been mostly disappointing so far (16,17), stimulating the search for alternative strategies that take therapeutic advantage of angiogenic neovessels. Here, we report first-in-human experiences with the targeted delivery of IL2 to the leukemia-associated vasculature and stroma using the immunocytokine F16-IL2 in heavily pretreated AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred three patients participated in the multicenter HOVON 43 16 trial, a randomized induction and postinduction therapy phase III study. Thirty-two patients participated in the multicenter HOVON 81 17 trial, a phase II multicenter study to assess the tolerability and efficacy of the addition of Bevacizumab to standard induction therapy of AML. These studies were approved by the medical ethics committee of the Erasmus Medical Center and were conducted in accordance with the Declaration of Helsinki.…”
Section: Selection Of Participantsmentioning
confidence: 99%